Reassessment of Acute and Chronic Toxicity Effects of Aqueous Leaf Extract of Morinda Lucida in Rattus Norvegicus - Saganuwan, S. A.; Aondoaver, A. D.; Roman, I. T. (Journal of Hematology Research, 2014)
In view of preponderance of medicinal uses of Morinda lucida there is need to reassess its toxicity potential. Phytochemical analysis of Morinda Lucida leaf powder was carried out to determine the therapeutic and toxic principles of the plant. Acute and chronic effects of aqueous extract of Morinda lucida leaf were studied in Rattus norvegicus. The phytochemical analysis revealed the presence of flavonoids, glycosides, saponins, anthraquinones, tannins, and reducing sugar, whereas steroids were absent. Proximate analysis yielded moisture (8.88%), dry matter (91.12%), ash (18.71%), fat and oil (25.16%), nitrogen free extract (34.30%), crude fibre (12.45%) and crude protein (10.50%). Median lethal dose (LD50) was estimated to be >16,265mg/kg body weight. Haematological analysis revealed significantly (P<0.05) increased packed cell volume, erythrocytes, haemoglobin, mean corpuscular haemoglobin and mean corpuscular haemoglobin concentration. However white blood cells decreased significantly (P<0.05) at dose level of 1,626.5mg/kg. But, alanine aminotrasferase, glucose, creatinine, total protein, bilirubin, sodium ion, bicarbonate ion and chloride ion decreased significantly (P<0.05). Urea increased significantly (P<0.05). Therefore, aqueous extract of Morinda lucida is safe at the test doses of 16.26 and 162.65mg/kg body weight when administered for 28 days with kidney degeneration and mild to moderate deleterious effects on lung, liver, heart and spleen at dose level of 1,626.5mg/kg bodyweight of the extract.